The meaning of baptism for the community of Jesus Christ: A declaration of the Theological Commission - Comissão Teológica da Confederação de Gnadau (Vox Scripturae - Revista Teológica Internacional, 2014)
The present text contains a theological declaration of the Gnadau Confederation Theological Commission, in Germany, on the matter of baptism. In a first moment, the authors present diverse arguments utilized by members of Christian communities to query the practice of infant baptism, besides mentioning other difficulties faced by Christian churches in relation to the baptismal practice. In a second moment, the authors develop a definition of what they understand by baptism and what it affects, according to the Reformation (in special Lutheran) and Pietistic theological tradition. On a third topic, diverse observations on the theology and baptismal practice made throughout the history of the church will be registered. On the forth topic, diverse dimensions that are part of the practical experience of baptism in the daily life of the Christian will be presented. And, lastly, a series of Scripture based counter-arguments and also from the theological tradition of the Reformation and Pietism will be made, in relation to the criticisms made in contemporaneity to baptism, in special to the practice of infant baptism.